2010
DOI: 10.4061/2011/925073
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of Intermolecular Interaction of Amyloid β Promoted on GM1 Micelles

Abstract: Clusters of GM1 gangliosides act as platforms for conformational transition of monomeric, unstructured amyloid β (Aβ) to its toxic β-structured aggregates. We have previously shown that Aβ(1–40) accommodated on the hydrophobic/hydrophilic interface of lyso-GM1 or GM1 micelles assumes α-helical structures under ganglioside-excess conditions. For better understanding of the mechanisms underlying the α-to-β conformational transition of Aβ on GM1 clusters, we performed spectroscopic characterization of Aβ(1–40) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 51 publications
2
52
0
Order By: Relevance
“…With large unilamellar vesicles, however, low POPC concentrations did not affect fibrillization kinetics markedly, but at higher POPC concentration, this lipid suppressed fibril formation. Thus, aggregation kinetics and the structure of the fibrillar products depend not only on lipid composition but also on physical factors such as radius of curvature of the surface …”
Section: Effects Of Lipid Surfaces and Other Amphiphilic Or Hydrophobmentioning
confidence: 99%
“…With large unilamellar vesicles, however, low POPC concentrations did not affect fibrillization kinetics markedly, but at higher POPC concentration, this lipid suppressed fibril formation. Thus, aggregation kinetics and the structure of the fibrillar products depend not only on lipid composition but also on physical factors such as radius of curvature of the surface …”
Section: Effects Of Lipid Surfaces and Other Amphiphilic Or Hydrophobmentioning
confidence: 99%
“…A previous study reported that the insertion of the C terminus of A␤ peptides that contained a series of hydrophobic amino acids into membranes was crucial to the structural conversion of monomeric A␤ peptides to amyloid fibrils (48). Moreover, the interface between the head groups and acyl chains of lipids was shown to be responsible for the binding and conformational conversion of A␤ peptides (49,50). Hence, a more detailed characterization of the relationship between the kinetics of A␤ fibrillation and hydrophobicity of liposomes will be important.…”
Section: -H)mentioning
confidence: 99%
“…Utsumi et al 43 showed that upon binding to gangliosidic micelles, Aβ40 exhibited an ‘up-and-down' topology, where the C-terminal dipeptide segment and two α-helices were in contact with the hydrophobic interior, whereas the remaining regions were exposed to the aqueous environment. 44 This interaction can induce Aβ oligomerization and fibril formation by promoting a change in Aβ conformation from α-helix to β-sheet. 45,46 Interestingly, cholesterol has been shown to enhance binding of Aβ to GM1 ganglioside clusters in lipid rafts providing a potential mechanism for endosomal Aβ accumulation in Nieman Pick type C, where genetic mutations disrupt the function of the lysosomal transporter protein NPC1 leading to the accumulation of cholesterol and glycolipids.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that ganglioside clusters may serve as a unique platform for binding of Aβ and the promotion of and transitioning the specific intermolecular interactions. 43,44 Therefore, increasing the activity of enzymes involved in ganglioside catabolism provide a novel approach to treating cerebral amyloidosis and other proteinopathies.…”
Section: Discussionmentioning
confidence: 99%